Graphics Overview - Edmund Arnold (Journal of Applied Communications, 1979)
You can not make a fish bite on a hook and you can not make a reader read your printed communication. The whole job of the editor immediately after something has been written is to put enough warm worms, if you will, on this reading job to cajole the reader into consuming his product whatever it is.